Tensile mechanical property of oil palm empty fruit bunch fiber reinforced epoxy composites - Ahmad Ghazilan, Ahmad Luqman; Mokhtar, Hanan; Shaik Dawood, Mohd. Sultan Ibrahim; Aminanda, Yulfian; Mohamed Ali, Jaffar Syed (Institute of Physics Publishing, 2017)
Natural, short, untreated and randomly oriented oil palm empty fruit bunch fiber reinforced epoxy composites were manufactured using vacuum bagging technique with 20% fiber volume composition. The performance of the composite was evaluated as an alternative to synthetic or conventional reinforced composites. Tensile properties such as tensile strength, modulus of elasticity and Poisson's ratio were compared to the tensile properties of pure epoxy obtained via tensile tests as per ASTM D 638 specifications using Universal Testing Machine INSTRON 5582. The tensile properties of oil palm empty fruit bunch fiber reinforced epoxy composites were lower compared to plain epoxy structure with the decrement in performances of 38% for modulus of elasticity and 61% for tensile strength.